Wind patterns as a potential driver in the evolution and maintenance of a North American migratory suture zone. (30th August 2016) - McCabe, Jennifer D.; Olsen, Brian J.; Hiebeler, David
Abstract : Suture zones are areas where range contact zones and hybrid zones of multiple taxa are clustered. Migratory divides, contact zones between divergent populations that breed adjacent to one another but use different migratory routes, are a particular case of suture zones. Although multiple hypotheses for both the formation and maintenance of migratory divides have been suggested, quantitative tests are scarce. Here, we tested whether a novel factor, prevailing winds, was sufficient to explain both the evolution and maintenance of the Cordilleran migratory divide using individual‐based models. Empirical observations of eastern birds suggest a circuitous migratory route across Canada before heading south. Western breeders, however, travel south along the Pacific coast to their wintering grounds. We modeled the effect of wind on bird migratory flights by allowing them to float at elevation using spatially explicit modeled wind data. Modeled eastern birds had easterly mean trajectories, whereas western breeders showed significantly more southern trajectories. We also determined that a mean airspeed of 18.5 m s –1 would be necessary to eliminate this difference in trajectory, a speed that is achieved by waterfowl and shorebirds, but is faster than songbird flight speeds. These results lend support for the potential importance of wind in shaping the phylogeographic history of North American songbirds.